Impact of colored shade netting on growth and physiological traits in avocado creole rootstock seedling - Bedoya-Ramírez, Sara Isabel; Loaiza-Ruiz, Ruby Alejandra; Barrera-Sánchez, Carlos Felipe; Córdoba-Gaona , Oscar de Jesús (Revista de Ciencias Agrícolas, 2024)
Photoselective netting is well-known for filtering the intercepted solar radiation and affecting light quality. However, more information is needed about how horticulture manipulation of light quantity and quality affects avocado rootstock seedlings’ growth and physiological traits. Therefore, this study aimed to investigate the effects of colored shading on the growth and development of avocado creole for planting production. A completely randomized experimental design with four treatments and five repetitions was used. The treatments included colored nets (red, black, white, and control – without a net). Net shading treatments affected leaf number, leaf area, leaf area index, rootstock diameter and length, dry matter, Dickson quality index, and all gas exchange variables. In contrast, specific leaf area and root length were not affected by the colored net. The red net generally increased the rootstock diameter and length, Dickson quality index, and net photosynthesis and water use efficiency more than the black, white net, and full sunlight growth conditions. This study reveals that changing the light intensity allows rootstock growth and physiological performance to be manipulated using different colored shade nets.